2022
DOI: 10.3389/fpsyg.2022.968513
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ emotional experience: Characteristics, dynamics and sources amid the teaching practicum

Abstract: Recently, teacher emotions have become the focus of research in teacher education. Teacher emotions not only affect teachers themselves but also have an impact on their students. However, pre-service teachers’ emotions have been neglected. This study is based on a qualitative analysis of online emotional diaries related to emotional experience expression by 120 Chinese pre-service teachers before, during, and after teaching practice. The results in this study show three characteristics of pre-service teachers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…By contrast, secondary school teacher candidates were found to have a greater sense of personal accomplishment. Concerning these ndings, Khoshhal et al (2017) state that during the preparation for a test, the onset of disruptive states is promoted driving individuals to emotional exhaustion (Ji et al, 2022). Similarly, getting good grades have been found to lead to an increase in personal accomplishment as well as in the academic self-concept (Paechter et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, secondary school teacher candidates were found to have a greater sense of personal accomplishment. Concerning these ndings, Khoshhal et al (2017) state that during the preparation for a test, the onset of disruptive states is promoted driving individuals to emotional exhaustion (Ji et al, 2022). Similarly, getting good grades have been found to lead to an increase in personal accomplishment as well as in the academic self-concept (Paechter et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-service teachers have a dual identity as both teachers and students during their teaching practice, which may affect their emotional states and behaviors as novice teachers. For instance, Xie and Jiang (2021) found that in-service teachers experienced more negative emotions than positive ones, while Ji et al, (2022) revealed that preservice teachers experienced more positive emotions than negative emotions overall.…”
Section: Limitations In Participantsmentioning
confidence: 99%
“…Emotional intelligence positively contributes to teachers' ability to interact with people from different backgrounds in terms of professional requirements, establish healthy relationships, control their emotions effectively, approach problems in a solution-oriented manner, and find happiness in their professional lives [40]. There are many studies [1,[41][42][43] examining the relationship between pre-service teachers and emotional intelligence. However, there is a scarcity of studies investigating the relationship between EI, AMO, and self-efficacy.…”
Section: The Current Studymentioning
confidence: 99%